The coupled 182W‐142Nd record of early terrestrial mantle differentiation. (18th June 2016) - Puchtel, Igor S.; Blichert‐Toft, Janne; Touboul, Mathieu; Horan, Mary F.; Walker, Richard J.
Abstract: New Sm‐Nd, Lu‐Hf, Hf‐W, and Re‐Os isotope data, in combination with highly siderophile element (HSE, including Re, Os, Ir, Ru, Pt, and Pd) and W abundances, are reported for the 3.55 Ga Schapenburg komatiites, South Africa. The Schapenburg komatiites define a Re‐Os isochron with an age of 3550 ± 87 Ma and initial γ 187 Os = +3.7 ± 0.2 (2SD). The absolute HSE abundances in the mantle source of the Schapenburg komatiite system are estimated to be only 29 ± 5% of those in the present‐day bulk silicate Earth (BSE). The komatiites were derived from mantle enriched in the decay products of the long‐lived 147 Sm and 176 Lu nuclides (initial ɛ 143 Nd = +2.4 ± 0.1, ɛ 176 Hf = +5.7 ± 0.3, 2SD). By contrast, the komatiites are depleted, relative to the modern mantle, in 142 Nd and 182 W (μ 182 W = −8.4 ± 4.5, μ 142 Nd = −4.9 ± 2.8, 2SD). These results constitute the first observation in terrestrial rocks of coupled depletions in 142 Nd and 182 W. Such isotopic depletions require derivation of the komatiites from a mantle domain that formed within the first ∼30 Ma of Solar System history and was initially geochemically enriched in highly incompatible trace elements as a result of crystal‐liquid fractionation in an early magma ocean. This mantle domain further must have experienced subsequent melt depletion, after 182 Hf had gone extinct, to account for the observed initial excesses in 143 Nd and 176 Hf. The survival of early‐formed 182 W and 142 Nd anomalies in the mantle until at least 3.55 Ga indicates that the products of early planetary differentiation survived both later planetary accretion and convective mantle mixing during the Hadean. This work moreover renders unlikely that variable late accretion, by itself, can account for all of the observed W isotope variations in Archean rocks. Key Points: Komatiites from the 3.55 Ga Schapenburg Greenstone Remnant in South Africa show coupled depletions in 142 Nd and 182 W The komatiites were derived from a mantle domain that formed within the first 30 Ma of Solar System history The products of early terrestrial differentiation survived planetary accretion and mantle mixing for 1.0 Ga